Intervenção com o videogame ativo gamificado: impacto sobre o perfil glicídico e o estado nutricional de adolescentes com excesso de peso - Guimarães, Anna Larissa Veloso (2020)
Introduction: overweight has been shown to be associated with energy imbalance caused by high caloric intake and physical inactivity, which can result in several metabolic changes, including on the glycidic profile. The interactive game has appeared as an intervention proposal, especially among young people, working in a playful way to promote physical activity. Objective: to evaluate the impact of the active video game, with the aid of gamification, on the glycidic profile and nutritional status of overweight or obese students. Methods: controlled intervention study carried out in the second half of 2018. The sample consisted of 70 overweight or obese adolescents, divided into two groups (control and experimental), aged between 10 and 16 years, enrolled bet ween the 5th and the 9th year of elementary school II in public schools in the municipality of Campina Grande - PB. Sociodemographic, lifestyle, nutritional status and biochemical variables were studied. Insulin resistance was determined using the TyG inde x: (triglycerides-glycemia: ([fasting triglycerides (mg / dL) x fasting glycemia (mg / dL))] / 2. The XBOX 360 platform was used to perform the intervention, with a Kinect accessory (Microsoft®), a general form was applied, weight was measured, height and waist circumference, and blood was collected. To increase the engagement of adolescents in the intervention activity, a gamification strategy was adopted. were analyzed in SPSS 22.0 and a significance level of 5% was adopted. To test the effect of the intervention on the proposed outcome, the chi-square test was applied; the distribution was tested by the Kolmogorov-Smirnov. the paired t-test was applied to abdominal adiposity. The study was approved by the Research Ethics Committee (CAAE: 84019518.3.0000.5187) registered in the Clinical Trials (NCT03532659) and REBEC (RBR-2xn3g6). Results: 36 adolescents were evaluated in the experimental group and 34 in the control. All were overweight, 40% were obese and 61.4% had abdominal adiposity. There was no change in fasting blood glucose. Eight (11.4%) adolescents showed an increase in glycolyzed hemoglobin and seven (10.0%) had insulin resistance. At the end of the intervention, eight overweight adolescents started to be classified as eutrophic, and the cases of o besity were higher in the control school (n = 16; 55.8%). In the experimental group, there was a reduction in the mean abdominal adiposity of almost 1 cm (p = 0.006). There was no impact on the glycidic profile. Conclusion: the intervention improved the z-score of BMI and reduced the metabolic adiposity of adolescents, but did not cause significant changes in the glycidic profile. Short -term programs are already capable of producing positive effects on nutritional status, but it is suggested to study interventions of longer duration for a better assessment of metabolic indicators.